Autoeficácia, catastrofização da dor e qualidade de vida em indivíduos com fibromialgia - Toledo, Laura Priscila Navarrete de (2015)
Fibromyalgia is defined as a syndrome characterized by chronic widespread musculoskeletal pain associated with a range of symptoms, including, sleep disturbances, fatigue, and emotional dysfunction are particularly frequent. This study is justified by the need for greater knowledge in the perception of fibromyalgia pain in our context and its impact on daily life, in addition to base the importance of measurement and evaluation of pain have to enable treatment. This study aimed to evaluate the perception of pain, self-efficacy beliefs, pain catastrophizing and the impact of the disease on quality of life of individuals with fibromyalgia and specific objectives characterize the sample in terms of sociodemographic, clinical and therapeutic data; measure the intensity of perceived chronic pain; characterize the fibromyalgia pain using pain descriptors; identifying the level of self-efficacy beliefs, quality of life and catastrophizing pain in people with fibromyalgia, according to the fields of instruments; investigate the relationship between pain intensity, self-efficacy beliefs, pain catastrophizing and quality of life in people with fibromyalgia and check the internal consistency of data collection instruments. The convenience sample consisted of patients as outpatients treated at a large hospital in a Family Health Unit of two cities in the interior, in addition to the open invitation to anyone who would participate through posters and brochures, all of which had medical diagnosis of fibromyalgia. Data collection was performed through structured interviews using the following instruments: collect sociodemographic data Instrument; Self-efficacy Scale for Chronic Pain (EAEDC) to assess the level of self-efficacy beliefs; Catastrophic Thoughts Scale of Pain (EPCD) to assess the level of pain catastrophizing; Fibromyalgia Impact Questionnaire (FIQ) to evaluate the impact of fibromyalgia on the quality of life of individuals and the Multidimensional Scale of Pain Assessment (EMADOR) for characterization of chronic pain. The study included 95 individuals, with an average of self-efficacy beliefs was 183.65 points, the index of catastrophic thoughts about pain was 2.20, the impact on quality of life was 67.20 and the intensity of pain was 7.36 points. There was high and negative association between beliefs of self-efficacy and pain catastrophizing, and moderate and negative association of self-efficacy beliefs with the intensity of pain. We also noticed a moderate association, but this positive turn of pain catastrophizing with pain intensity. The keywords that best described the pain so classified as evaluative. These findings indicate that possibly people with fibromyalgia have other dimensions affected by pain that not only the physical and, therefore, health professionals need to conduct a comprehensive assessment of pain perception in order to propose their appropriate management.